Hidrogen Hijau Berbasis Biomassa Sebagai Strategi Transisi Menuju Kemandirian Energi dan Pembangunan Berkelanjutan di Indonesia: Biomass-Based Green Hydrogen As A Transition Strategy Towards Energy Independence And Sustainable Development In Indonesia - Hartomo, Ariawan; Yanto, Sri; Murtiana, Sri (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Indonesia’s heavy reliance on fossil fuels where renewable energy contributes only about 13–14% of the national energy mix in 2024 continues to accelerate carbon emissions and expose the economy to global price volatility. Transitioning toward clean energy has therefore become a strategic necessity for national sustainability. This study aims to analyze Indonesia’s biomass potential, assess its contribution to sustainable development, and formulate policy directions and cross-sector collaboration to accelerate an inclusive and sustainable green energy transition. The research employs a semi-systematic literature review of more than 40 scientific publications, policy reports, and national datasets (ESDM, IRENA, BPS) using the Triple Bottom Line framework (People, Planet, Profit). Findings reveal that Indonesia’s biomass potential exceeds 146 million tons per year, capable of producing 50–60 million tons of green hydrogen substituting approximately 35% of national primary energy demand. CaO–Ni-based gasification technology demonstrates 70–85% conversion efficiency and up to 90% emission reduction compared to fossil fuels. Moreover, green hydrogen development can generate green jobs, strengthen local economies, and support the 2060 Net Zero Emission target. This study underscores the importance of pentahelix collaboration, green fiscal policies, and technological innovation to establish an inclusive, competitive, and sustainable green hydrogen ecosystem in Indonesia.